Activated CD4+ T cells enter the splenic T‐cell zone and induce autoantibody‐producing germinal centers through bystander activation. Issue 1 (4th November 2013) - Banczyk, David; Kalies, Kathrin; Nachbar, Lars; Bergmann, Lars; Schmidt, Philipp; Bode, Ulrike; Teegen, Bianca; Steven, Philipp; Lange, Tanja; Textor, Johannes; Ludwig, Ralf J.; Stöcker, Winfried; et al.
<x xml:space="preserve">Abstract</x> CD4+ T (helper) cells migrate in huge numbers through lymphoid organs. However, little is known about traffic routes and kinetics of CD4+ T‐cell subsets within different organ compartments. Such information is important because there are indications that CD4+ T cells may influence the function of microenvironments depending on their developmental stage. Therefore, we investigated the migration of resting (naïve), activated, and recently activated (memory) CD4+ T cells through the different compartments of the spleen. Resting and recently activated CD4+ T cells were separated from thoracic duct lymph and activated CD4+ T cells were generated in vitro by cross‐linking the T‐cell receptor and CD28. The present study shows that all three CD4+ T‐cell subsets selectively accumulate in the T‐cell zone of the spleen. However, only activated T cells induce the formation of germinal centers (GCs) and autoantibodies in rats and mice. Our results suggest that in a two‐step process they first activate B cells independent of the T‐cell receptor repertoire and CD40 ligand (CD154) expression. The activated B cells then form GCs whereby CD154‐dependend T‐cell help is needed. Thus, activated T cells may contribute to the development of autoimmune diseases by activating autoreactive B cells in an Ag‐independent manner.